BAFF and APRIL immunotherapy following Bacille Calmette-Guérin vaccination enhances protection against pulmonary tuberculosis in mice - Xie, Min; Tsai, Chen-Yu; Woo, Joshua; Nuritdinov, Frank; Cristaldo, Melissa; Odjourian, Narineh M.; Antilus-Sainte, Rosleine; Dougher, Maureen; Gengenbacher, Martin (Frontiers in Immunology, 2025)
IntroductionBacille Calmette-Guérin (BCG), the only tuberculosis vaccine currently in clinical use, provides inadequate long-term protection. Administered at birth, BCG induces broad immune responses against a large number of antigens shared with Mycobacterium tuberculosis (Mtb), but protection wanes over time. We have previously shown that unconventional B cell subsets play a role in tuberculosis control.MethodsHigh-dimensional flow cytometry and multiplex cytokine analysis were employed to investigate the effects of immunotherapy on BCG-vaccinated mice in an Mtb challenge model.ResultsIn this study, we investigate the potential of recombinant cytokines targeting B cells – B-cell activating factor (BAFF) and A proliferation-inducing ligand (APRIL) – to modulate BCG immunity and improve protection in mice. Both cytokines play overlapping roles in B cell development and peripheral survival. Following subcutaneous BCG vaccination, immunotherapy with BAFF or APRIL resulted in an increased frequency of unconventional B cells potentially transitioning into antibody-producing plasma cells. Concurrently, we observed an increased frequency of central memory T cells, a subset critical for protective immunity. Changes in cellular immune responses were accompanied by reduced pro-inflammatory cytokine profiles and a contraction of the leukocyte population in lungs. Importantly, mice receiving BCG vaccination followed by BAFF or APRIL immunotherapy exhibited superior long-term protection against pulmonary tuberculosis relative to controls that received only BCG.ConclusionIn summary, our findings demonstrate that combining BCG vaccination with B cell targeted immunomodulatory therapies can improve long-term protection against pulmonary tuberculosis, highlighting the continued relevance and underutilized potential of BCG as a vaccine platform.